Capillary wetting and interfacial phenomena in microstructures - Radiom, Milad (2010)
Fluid penetration into capillary tubes resulting from the interplay between solid-liquid adhesive interactions and liquid-liquid cohesive interactions is a ubiquitous phenomenon. In nature, the rise of underground water in the soil is due to capillary pressure. Moreover, a wide variety of technological applications, e.g. oil extraction through porous rocks, washing process with detergents, surface coating etc, are based fundamentally on capillarity effects. As a result, studies with respect to the physics of capillary flows, both from the engineering and applied sciences and from a theoretical point of view, have been constantly renewed for almost a century.